Quality of life after cancer—How the extent of impairment is influenced by patient characteristics. Issue 1 (December 2016) - Peters, Elisabeth; Mendoza Schulz, Laura; Reuss-Borst, Monika
Abstract Background Although this effect is well known, tailored treatment methods have not yet been broadly adopted. The aim of this study was to identify those patient characteristics that most influence the impairment of quality of life and thus to identify those patients who need and can benefit most from specific intervention treatment. Methods 1879 cancer patients were given the EORTC QLQ C-30 questionnaire at the beginning and end of their inpatient rehabilitation. Patients' scores were compared to those of 2081 healthy adults (Schwarz and Hinz, Eur J Cancer 37:1345–1351, 2001). Furthermore, differences in quality of life corresponding to sex, age, tumor site, TNM stage, interval between diagnosis and rehabilitation, and therapy method were examined. Results Compared to the healthy population, the study group showed a decreased quality of life in all analyzed domains. This difference diminished with increasing age. Women reported a lower quality of life then men in general. Patients with prostate cancer showed the least impairment in several domains. Patients having undergone chemotherapy as well as radiotherapy were impaired the most. Surprisingly, TNM stage and interval between diagnosis and rehabilitation did not significantly influence quality of life. Global quality of life and all functional domains significantly improved after a 3-week rehabilitation program. Conclusions Despite an individualized and increasingly better tolerable therapy, the quality of life of cancer patients is still considerably impaired. However, systematic screening of psychosocial aspects of cancer, e.g. quality of life, could enable improved intervention.